The Usage of Recycle Materials for Science Practicum: Is There Any Effect on Science Process Skills? - Setiyo Prajoko; Mohamad Amin; Fatchur Rohman; Muhana Gipayana (Institute of Advanced Engineering and Science, 2017)
This study aimed at determining the effect of recycle materials usage for science practicum on students' basic science process skills of the Open University, Surakarta. Recycle materials are the term used for the obtained materials and equipment from the students’ environment by taking back the garbage or secondhand objects into goods or new products which have a benefit for practicum activities. Randomized posttest only control group design was applied in this study and involving 83 students which divided into experimental class and control class. Collected data were science process skills test and questionnaire. The results of this study obtained Kruskal Wallis test result of 0.000<0.05. So, there was effect of recycle materials usage for science practicum on students’ science process skills. Students also provided positive feedback on the use of recycle materials for science lab activities.